Eel migration - results from tagging studies with relevance to management - Sjöberg, Niklas B. (Stockholms universitet, Institutionen för ekologi, miljö och botanik, 2015)
In response to the drastic decline of the European eel (Anguilla anguilla (L.)) fisheries have been reduced and elvers are stocked in areas where natural abundances are low. Are these measures adequate? To answer different aspects of this question, we have analysed more than a century of eel tagging, using both traditional and more novel capture – recapture analyses. Based on these long-term data, we have evaluated the impact of the Swedish eel coastal fisheries using Survival analysis. Our analysis indicates that the fishing mortality just prior the 2009 fishing restrictions were in the order of 10%. More recent tagging programs have focused on issues related to the fate of stocked fish. If and how they migrate out of the Baltic Sea and further on towards the Atlantic Ocean. Both earlier and our new studies reveal that all eels recaptured on the Swedish East Coast, no matter of their origin, migrate at a reasonable speed and direction towards the outlets of the Baltic Sea. Even though it is sometimes difficult to determine their origin, our analyses indicate that stocked fish were scarce among the recaptures. In an experiment on the Swedish West Coast, we knew the individuals’ origin (stocked or wild) and they had similar migration patterns. In contrast, silver eel in Lake Mälaren – assumed to have been stocked as elvers or bootlace eels – seemed to have difficulties in finding the outlets. Instead they overwintered and lost weight. However, weight losses are also significant among non-stocked individuals in the Baltic Sea, both if they overwinter and if they appear to be on their way out from the area. It remains an open question whether eels from the Baltic region in general, and whether the overwintered fish in particular, manage to reach the spawning area in the Atlantic Ocean. Based on current knowledge, I advocate invoking the precautionary approach and to concentrate Swedish eel stockings to the West Coast and allow the young fish to spread out on their own. At the time of the doctoral defense, the ...